2011
DOI: 10.1021/ic102385p
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide Nitrate Complexes of Tri-Isobutylphosphine Oxide: Solid State and CD2Cl2 Solution Structures

Abstract: The complexes Ln(NO(3))(3)L(3) between Ln(NO(3))(3) and (i)Bu(3)PO (=L) have been prepared for Ln = La-Lu (excluding Pm). The isolated complexes have been characterized by infrared spectroscopy, mass spectrometry, and elemental analysis. The single crystal X-ray structures have been determined for representative complexes across the series Ln = Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Tm, and Yb and show the coordination geometry around the metal to be the same with 9-coordinate lanthanide ions and bidentate nitrates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Unfortunately, any t, including the two-, three-and four-legged scattering paths resulted in bad ts of this peak which might be due to highly distorted paths lengths. 47,48 The best t was obtained by including only the two-legged scattering path Ln-P. This resulted in a coordination number of 4.5(4), a DebyeWaller factor of 0.01(1)Å 2 and a path length of 3.788(7)Å.…”
mentioning
confidence: 99%
“…Unfortunately, any t, including the two-, three-and four-legged scattering paths resulted in bad ts of this peak which might be due to highly distorted paths lengths. 47,48 The best t was obtained by including only the two-legged scattering path Ln-P. This resulted in a coordination number of 4.5(4), a DebyeWaller factor of 0.01(1)Å 2 and a path length of 3.788(7)Å.…”
mentioning
confidence: 99%
“…4 The single crystal X-ray structures and solution properties of pentagonal 5 bipyramidal complexes [Ln(H 2 O) 5 a b s t r a c t 24 The products of the reactions of tricyclohexlyphosphine oxide, Cy 3 PO = L, with lanthanide chlorides 25 (Ln = La, Dy, Er, Yb) have been investigated by solution NMR spectroscopy and single crystal X-ray crys- 26 tallography (Dy, Er). The structures of the complexes are based on a pentagonal bipyramidal arrangement 27 around the central Ln 3+ ion with two Cy 3 PO in axial positions and five water molecules in the equatorial 28 plane with molecular formulae LnL n (H 2 O) 5 ÁLÁ3ClÁH 2 OÁEtOH.…”
mentioning
confidence: 99%
“…It is interesting that the temperature dependence in the Mes3PO / Ln 3+ systems is opposite of that found for 31-P shift for phosphine oxides directly bonded to lanthanides [7,8], but the same as for phosphine oxides hydrogen bonded to lanthanide coordinated water molecules. In the absence of crystallographic data from isolated compounds it is not possible to be certain of the nature of this interaction, but hydrogen bonding to the coordinated water molecules, as previously observed with other sterically crowded phosphine oxides [11,12] seems reasonable.…”
Section: Solution Nmr Investigationmentioning
confidence: 72%
“…We have previously studied the effect on structures and solution properties of increasing the size of the R group in R3PO where we found that solid state structures and solution properties depend on a balance between steric and electronic effects of the phosphine oxides and the size of the lanthanide ions [6][7][8]. Cone angles, are not available for phosphine oxides, and as a result we have used the cone angles of the parent phosphine [9] as a proxy for the steric demands of the oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation